Cultural Identity Changes in The Girl with Seven Names: A Critical Analysis of An Immigrant’s Experiences - Amelia Ivana Limantra; Ikwan Setiawan; Nurhadianty Rahayu (Language Circle: Journal of Language and Literature, 2026)
This study focuses on cultural identity and cultural changes that are experienced by the main character in the memoir The Girl with Seven Names written by Hyeonseo Lee. This study follows Hall's (1996) theory about cultural identity in the process of becoming rather than being. There are three scopes of study in analyzing cultural identity, including: how is the process of cultural identity constructed; the cultural disparities in achieving social status between South Korea and North Korea; and the criticism toward North Korea. Using a textual approach, the data were analyzed after the researchers did a series of close reading. The results reveal the struggle of the main character’s process of identity becoming as an immigrant in surviving the host culture to form a new identity as a North Korean defector. The findings also showed that this memoir was used as a form of criticism toward the North Korean government whose politics and class system restrict its people’s freedom.